Caracterização óptica e eletrônica de filmes semicondutores usando espectros de transmitância e refletância - Azevedo, Carlos Guilherme Gonçalves de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This work presents the end result of the developmet of a method for calculation of optical constants of semiconductor films based on measured transmitance (T) and reflectance (R), which allows the calculation of the spectral optical constants in the range of 0.5 eV to 5.0 eV, with possible extension to the middle and far infrared and the ultraviolet. The calculation method consists in the use of R spectra to improve and extend the determination of the values of the refractive index (n) and extinction coefficient (k). As a first approximation, the method is based on the T spectrum to calculate the n values in the spectral region of the interference fringes and the k values across the spectral range of T, as done in other methods. The improvement realized is related to the use of k values calculated initially from T spectrum, and aproximated n values - extrapolating the values obtained in the region of the interference fringes, to calculate refined n values using the R spectrum in the high absorption region. The method makes possible to determine the k values across the range in which the measured values T have good degree of accuracy. Another advantage observed in the present method is the possibility of refining the values of the optical constants using the R and T spectra alternately. The use of R enables a better fit to the n values, particularity the high absorption region (or anomalous dispersion region), while T spectra allow refined calculations of k, mainly above the bandgap, and the dispersion of the refractive index in low absorption. The calculations use the complete expressions for transmittance and reflectance, derived directly from Maxwell's equations. The expression used take into account the coherent multiple reflections in the films and incoherent in the substrate. The experimental work involved the transmittance measurements at a range of energy from 0.38 eV to 6.20 eV nm and reflectance measurement using integrating...

Neste trabalho apresenta-se um método para cálculo de constantes ópticas de filmes semicondutores baseado em medidas de transmitância (T) e refletância (R) na faixa espectral entre 0,50 eV, com possível extensão par a região do infravermelho médio e distante e para o ultravioleta. O método consiste na utilização dos espectros de R para melhorar a estender a determinação dos valores do índice de refração (n) e do coeficiente de extinção (k). Como uma primeira aproximação, o método é baseado no espectro de T para calcular os valores de n na região espectral das franjas de interferência e de (k) em toda a faixa do espectro de T, como feito em outros métodos. A melhoria realizada está relacionada ao uso dos valores aproximados de n - da extrapolação dos valores obtidos na região das franjas de interferência, para calcular valores refinados de n usando o espectro de R na região de alta absorção. O método possibilita determinar os valores de k em toda faixa na qual os valores medidos de T tenham bom grau de exatidão. Outra vantagem é a possibilidade de refinamento dos valores das constantes ópticas utilizando os espectros de R e T alternadamente. O uso de R possibiita um ajuste melhor dos valores de n, principalmente na região de alta absorção (dispersão anômala) enquanto os espectros de T permitem cálculos refinados de K, principalmente para valores acima do bandgap, e a dispersão do índice de refração em baixa absorção. São utilizadas expressões completas para transmitância e refletância, derivadas diretamente das equações de Maxwell, as quais levam em conta as reflexões múltiplas coerentes nos filmes e as incoerências nos substratos. O trabalho experimental envolve a deposição de amostras de TiO2 pela técnica de sputering reativo e medidas de transmitância na faixa de energia de 0,38 eV a 6,20 eV e medidas de refletância usando esfera integradora entre 0,50 eV a 4,96 eV. Para testar...
Optical and electronic characterization of semiconductor films using transmittance and reflectance spectra
Keywords: Filmes semicondutores; Metodologia; Unidades; Refração; Absorção; Semiconductor films